How do I factor the following question?
First find the factors of 7 (1,7) and ( -1, -7) when trying to factor the question the constant is the main number to focus on because the factors of that number will also make up the second variable. If there is no way to factor the constant and get the second variable as well then there is no way to factor the problem. Below are two different results based on factoring using this method.
(X-1) (X-7) = X^2-7x-x+7 = X^2-8x+7
(X+1) (X+7)= x^2+7x+x+7= x^2+8x+7